2019
DOI: 10.1016/j.aquatox.2019.105325
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal exposure to copper supresses the ability to acclimate to hypoxia in a model fish species

Abstract: HighlightsExposure to hypoxia resulted in acclimation by G. aculeateus, demonstrated by a reduction of their critical oxygen level.In the presence of copper, the capacity to reduce the critical oxygen tension following hypoxia was prevented.Combined exposure of copper and hypoxia resulted in an increase expression of mt1 and hif1α transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
6
1
Order By: Relevance
“…2A). This contrasts recent findings in three-spined stickleback (Gasterosteus aculeatus), in which waterborne copper exposure (20 μg/l) impaired improvements in Pcrit that result from hypoxia acclimation (Fitzgerald et al, 2019). Pcrit is often considered to reflect the ability to extract oxygen from the environment during hypoxia, and is considered to be a useful indicator of hypoxia tolerance in many species (Regan et al, 2019;Rogers et al, 2016;Speers-Roesch et al, 2013).…”
Section: Wastewater Exposure Disrupts Responses To Chronic Hypoxiacontrasting
confidence: 73%
“…2A). This contrasts recent findings in three-spined stickleback (Gasterosteus aculeatus), in which waterborne copper exposure (20 μg/l) impaired improvements in Pcrit that result from hypoxia acclimation (Fitzgerald et al, 2019). Pcrit is often considered to reflect the ability to extract oxygen from the environment during hypoxia, and is considered to be a useful indicator of hypoxia tolerance in many species (Regan et al, 2019;Rogers et al, 2016;Speers-Roesch et al, 2013).…”
Section: Wastewater Exposure Disrupts Responses To Chronic Hypoxiacontrasting
confidence: 73%
“…Copper exposure has been shown to interfere with aquatic organisms' ability to deal with other stressors. Fitzgerald et al (2019) found that Cu exposure prevented sticklebacks ( Gasterosteus aculeatus ) from acclimating to hypoxia, which may be due to Cu's ability to suppress the cortisol stress response in fish. This makes it more difficult for the fish to respond to concurrent stressors (Nascimento et al, 2012; Tellis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Research into how hypoxic conditions affect the physiology of aquatic organisms and their ability to cope with chemical toxicity is much needed given the large (and increasing) expanse of surface waters experiencing such conditions. Recent studies on interactions between hypoxia and metal toxicity in zebrafish and threespined stickleback highlight the potential for major impacts of environmental oxygen (Fitzgerald et al, 2016(Fitzgerald et al, , 2019Fitzgerald, Katsiadaki & Santos, 2017). For example, hypoxia halved the toxicity of copper during a continuous 4-day exposure in zebrafish embryos.…”
Section: ) Oxygenmentioning
confidence: 99%